Prevalence and Associated Factors of Dysmenorrhea Among University Students in Tamil Nadu, India: A Cross-Sectional Study - Benson Thomas M; Daniyal J; Venmathy S; Kowsalya B; Janmejaya Samal (National Journal of Community Medicine)
Introduction: Dysmenorrhea is a common gynaecological condition of uterine origin characterised by excruciating menstrual cramps. For more than 50% of menstruating women primary dysmenorrhea is both a clinical and a social problem. A cross-sectional study was conducted to estimate the prevalence and determine the factors associated with dysmenorrhoea among university students in Tamil Nadu.